Assessing functions of stimuli associated with rich‐to‐lean transitions using a choice procedure. Issue 1 (1st July 2019) - Langford, Jeremy S.; Pitts, Raymond C.; Hughes, Christine E.
Abstract : Under fixed‐ratio schedules, transitions from more to less favorable conditions of reinforcement (rich‐to‐lean transitions) usually generate extended pausing. One possible explanation for this effect is that stimuli associated with rich‐to‐lean transitions are aversive and, thus, extended pausing functions as escape. The purpose of this study was to characterize further the aversive function of different transitions, and the stimuli associated with them, by allowing pigeons to choose to complete select ratios in the presence of either a mixed‐schedule stimulus or a transition‐specific multiple‐schedule stimulus. The mixed schedule was preferred during transitions that signaled an upcoming lean reinforcer (rich‐to‐lean and lean‐to‐lean), whereas the multiple schedule was preferred during transitions that signaled an upcoming rich reinforcer (lean‐to‐rich and rich‐to‐rich). These findings support the notion that stimuli associated with rich‐to‐lean (and to some extent lean‐to‐lean) transitions can function aversively; whereas stimuli associated with other transitions (e.g., lean‐to‐rich and rich‐to‐rich) can function as conditioned reinforcers. When the opportunity to choose between schedule‐correlated stimuli was available, however, choice latency was controlled exclusively by the multiple‐schedule stimulus. That is, the opportunity to select the mixed schedule did not attenuate rich‐to‐lean pauses, suggesting that extended pausing may be more than simply escape.